Constructing Serious Creativity Scale for Athletes - Razzaq Waheeb Yaseen, Abdul; Abdul Ameer Darweesh, Yousif; Hasballah Ibrahim, Muslim (International Journal of Psychosocial Rehabilitation, 2020)
The study problem is the lack of an Iraqi sport scale tool in the field of sport to measure serious creativity. It aims to build a scale model of serious creativity of the applicants to individual and team sports in Iraq. A descriptive method with a survey was used to build the scale. The study participants were a random sample of 425 sportspeople using De Bono’s model to identify the concept, dimensions, and phrases of serious creativity. The final form of the scale after meeting the conditions of authenticity, consistency, and capacity to distinguish 52 items. The items are divided into 6 dimensions, which are challenge, mental motivation, reason, liberation, fluency, style of thinking, and synchronization. The researchers recommend using a scale to determine serious creativity and benefiting from the results to instruct and train the sportspeople whose serious creativity is low. The correlations between serious creativity and other variables such as worry, ego, and psychological security, etc., might be investigated.